Working on freedom from want - Abd Razak, Dzulkifli (2008)
THE Merdeka celebrations this year have been scaled down to reflect the current economic reality. The worldwide downturn will be lingering a while longer, impacting many economies. It is befitting that we are observing the nation's independence with some measure of restraint. Already, it is very heartening to note that the Federal Government's external debt has reached a new low of RM19.6 billion, or 7.3 per cent of the total debt, as of Dec 31 last year.